Florid Cemento-Osseous Dysplasia with a Concurrent Glandular Odontogenic Cyst - Kungoane, Tsholofelo (Head Neck Pathol, 2020)
The presence of non-odontogenic cysts associated with benign fibro-osseous lesions of the jaws has been well documented. However, literature is scant when describing benign fibro-osseous lesions with associated odontogenic cysts. This case report highlights the presence of a concurrent developmental odontogenic cyst, glandular odontogenic cyst with extensive squamous metaplasia, in a patient with florid cemento-osseous dysplasia (COD). The postulated pathogenesis of these synchronous lesions is discussed along with a review of current literature. Surgical treatment is discouraged for florid COD, however, radiological follow-up is recommended, especially in lesions with associated cysts.